Homogenization of historical series of population entities and demographic challenge: evolution of the settlements of Aragon (Spain) between 1857 and 2022.: Article - Esteban Rodríguez, Samuel (Geographicalia, 2023)
In Spain, the concept of population entity has varied over time. This, in the historical series of entities, represents a source of noise that makes the study of long-term changes difficult. Taking the Community of Aragon as the study area, during the period 1857-2022, the series of number of entities is reconstructed and a technique is tested to homogenize it. This procedure, which takes into consideration some ideas from the Theory of Central Places, is based on the establishment of urban hierarchies based on the demographic position of the settlement within the urban system. This has allowed us to identify the type of settlements with the most variations; In addition, have a homogenized series with the evolution of the inhabited entities. Considering the changes in the habitat and the trend that each area presents is essential to address policies against the Demographic Challenge efficiently.
Keywords: Demographic challenge; habitat; depopulation; urban hierarchy; settlement system